Initial outcomes of endovenous laser ablation with 1940 nm diode laser in the treatment of incompetent saphenous veins. (February 2019) - Park, Insoo
Objectives: To investigate the initial outcomes of 1940 nm diode laser in the treatment of incompetent saphenous veins. Methods: This was a prospective observational study. We treated 89 patients with 160 incompetent saphenous veins using a 1940 nm diode laser and bare fiber. The laser's power was set to 4.5 W with a mean linear endovenous energy density of 50.4 J/cm. Results: The one-month closure rate was 100%. The post-procedural pain score at 6 h, 1 day, 10 days, and 1 month was 0.85 ± 1.04, 0.65 ± 1.01, 0.82 ± 1.25, and 0.47 ± 0.82, respectively. Complications encountered included paresthesia (3.8%) and thrombophlebitis (4.4%), whereas no cases of endovenous heat-induced thrombosis were observed. Conclusion: The 1940 nm laser and bare fiber at 50.4 J/cm showed satisfactory initial outcomes with less pain and fewer complications, in the treatment of incompetent saphenous veins.